2019
DOI: 10.1002/term.2829
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulsed electromagnetic fields and electromagnetic fields tuned to the ion cyclotron resonance frequency of Ca2+on chondrogenic differentiation

Abstract: Previous studies provide strong evidence for the therapeutic effect of electromagnetic fields (EMFs) on different tissues including cartilage. Diverse exposure parameters applied in scientific reports and the unknown interacting mechanism of EMF with biological systems make EMF studies challenging. In 1985, Liboff proposed that when magnetic fields are tuned to the cyclotron resonance frequencies of critical ions, the motion of ions through cell membranes is enhanced, and thus biological effects appear. Such e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The stimulation of PEMF could increase intracellular calcium concentration by regulating calcium channels, which are required for the chondrogenic differentiation of MSCs [ 31 ]. When the parameters of EMF were tuned to the cyclotron resonance frequencies of calcium ions, Kavand et al reported an enhanced efficacy of chondrogenesis [ 33 ]. Recently, one study showed that the MSC-derived conditioned medium post EMF exposure was also capable to promote cartilage regeneration and demonstrated that EMF could regulate the paracrine function of MSCs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of PEMF could increase intracellular calcium concentration by regulating calcium channels, which are required for the chondrogenic differentiation of MSCs [ 31 ]. When the parameters of EMF were tuned to the cyclotron resonance frequencies of calcium ions, Kavand et al reported an enhanced efficacy of chondrogenesis [ 33 ]. Recently, one study showed that the MSC-derived conditioned medium post EMF exposure was also capable to promote cartilage regeneration and demonstrated that EMF could regulate the paracrine function of MSCs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, increasing evidence has demonstrated that physical stimuli such as electromagnetic fields (EMF) could promote chondrogenic differentiation of BMSCs [ 31 ]. The EMF exposure induced chondrocyte proliferation and differentiation, and ECM synthesis by variable potential mechanisms, including regulating calcium channel in cell membrane [ 32 , 33 ], increasing transforming growth factor beta (TGFβ) and bone morphogenetic protein 2 (BMP2) expressions [ 34 , 35 ], and modulating MSCs secretome and paracrine function [ 36 ]. Stefani et al [ 37 ] reported that EMF stimulation improved repair and integration of engineered constructs in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of PEMF could increase intracellular calcium concentration by regulating calcium channels, which are required for the chondrogenic differentiation of MSCs [31]. When the parameters of EMF were tuned to the cyclotron resonance frequencies of calcium ions, Kavand et al reported an enhanced e cacy of chondrogenesis [33]. Recently, one study showed that the MSC-derived conditioned medium post EMF exposure was also [71].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, increasing evidence has demonstrated that physical stimuli such as electromagnetic elds (EMFs) could promote chondrogenic differentiation of BMSCs [31].The EMF exposure induced chondrocyte proliferation and differentiation, and ECM synthesis by variable potential mechanisms, including regulating calcium channel in cell membrane [32,33], increasing transforming growth factor beta (TGFβ) and bone morphogenetic protein 2 (BMP2) expressions [34,35], and modulating MSCs secretome and paracrine function [36]. Stefani et al [37] reported that EMF stimulation improved repair and integration of engineered constructs in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of endoplasmic reticulum stress, Ca 2+ is released into the cytoplasm, resulting in increased intracellular Ca 2+ concentration. It has been reported that the endoplasmic reticulum “perceives” magnetic information by the magnetic spin dynamics of the Ca 2+ protein channel reaction induced by eddy currents [23, 24]. Identification of inhibitory osteoblasts exhibiting magnetic induction behavior within the endoplasmic reticulum represent the first practical experimental evidence that Ca 2+ is required for magnetic induction pathways in bone development [25, 26].…”
Section: Introductionmentioning
confidence: 99%